Ontogeny of CX3CR1-EGFP expressing cells unveil microglia as an integral component of the postnatal subventricular zone - Xavier, Anna L.; Lima, Flavia R. S.; Nedergaard, Maiken; Menezes, João R. L. (Frontiers in Cellular Neuroscience, 2015)
The full spectrum of cellular interactions within CNS neurogenic niches is still poorly understood. Only recently has the monocyte counterpart of the nervous system, the microglial cells, been described as an important cellular component in neurogenic niches. The present study sought to characterize the microglial population in the early postnatal subventricular zone (SVZ), the major site of postnatal neurogenesis, and in its anterior extension, the rostral migratory stream (RMS), a pathway for neuroblasts during their transit toward the olfactory bulb (OB) layers. Analysis of the transgenic mice strain that has one of the locus of the constitutively expressed fractalkine CX3CR1 receptor replaced by the gene encoding the green fluorescent protein (EGFP) circumvented the antigenic plasticity of the microglial cells. Here we show that common phenotypic markers of microglia do not reveal the full complement of these cells within the SVZ/RMS pathway. Remarkably, our analysis show that within the early SVZ/RMS pathway microglia are not proliferative and display a protracted development, retaining a more immature morphology than their counterparts outside germinal layers. Furthermore, during the first postnatal days microglia contact and phagocyte radial glia cells (RGs). Our results unveil microglial cells as a prominent component along the entire SVZ niche, together with neuroblasts and astroglial progenitors.